The Prevalence of Cytomegalovirus, Hepatitis B, Hepatitis C, and HIV Infections among Hemophilic Patients in Sanandaj in 2017 - Sohrabi, Nasrollah (Asian Journal of Pharmaceutics (AJP), 2018)
Background and Objective: As Cytomegalovirus (CMV) has been distributed widely and great number of people are affected by it, such as hemophilic patients, and given the prevalence and complications of CMV, hepatitis B, hepatitis C, and HIV and lack of study in Kurdistan province in this regard, this study was conducted to evaluate the prevalence of CMV infection and other viruses among the hemophilic patients. This study can be used to reduce and solve the problem of hemophilic patients and health system plans. The objective of this study was to evaluate the prevalence of mentioned infections among hemophilic patients in Besat Hospital in Sanandaj in 2017. Materials and Methods: This is a descriptive study in which its population included all 121 hemophilic patients, diagnosed in Besat Hospital of Kurdistan province. They were examined in terms of infection of four viruses, including hepatitis C, hepatitis B, CMV, and HIV. It should be noted that the definition of infection was based on global criteria. Results: Of 121 patients, 95 cases were tested for hepatitis C, which 22 of them (23.1%) were positive in terms of HCV-Ab, and 13 people (13.6%) were suspected. In addition, 88 of them were tested for CMV, which 70 of them (79.5%) were positive in terms of CMV-Ab. In terms of HIV and HBV, all tested patients were seronegative. Among these patients, 48 patients had severe hemophilia, who recurrently received coagulation factor. Among them, 14 people (29.1%) were seronegative in terms of HCV-Ab, and 43 people (89.5%) were seronegative in terms of CMV-Ab. In addition, nine of them (18.7%) were suspected in terms of HCV-Ab.Conclusion: The recent study showed that the prevalence of hepatitis C among hemophilic patients is higher than that in other people of the community. In addition, among hemophilic patients, the prevalence of hepatitis C is higher in patients who received coagulation factor recurrently than that in other patients. The prevalence of CMV is also more in patients receiving factor recurrently than that in rest of the patients. Therefore, patients receiving blood and blood products should be periodically evaluated for virology.